ASSESSMENT ON THE EFFECT OF EXECUTIVE FUNCTIONING DISORDERS IN VULNERABILITY TO DEPRESSION AMONG ADOLESCENTS IN SECONDARY SCHOOLS IN MERU COUNTY, KENYA - Kiambarua, Kenneth Gitiye; Mwiti, Peter Mwiti; Thuba, Esther Thuba (Journal of Advanced Psychology, 2022)
Purpose: Assessment on the effect of executive functioning disorders in vulnerability to depression among adolescents in secondary schools in Meru County, Kenya. Methodology: The study adopted descriptive research design to gather both qualitative and quantitative data. Secondary schools were sampled using proportionate stratified sampling method to obtain 27 secondary schools in Meru County. The principals/deputy principals and counseling teachers were interviewed. Mathematics and English teachers answered a questionnaire, while the students were assessed using depression tool. Pretesting of data collecting instruments was done in 3 schools in the neighboring Tharaka Nithi County; Ikuu girls' secondary school, Chuka boys' high school and Ndagani mixed day secondary school. Data was analyzed using descriptive statistics such as frequency, percentage and median. Additionally, inferential statistics such as linear regression and multiple regressions inclusive of regression coefficients were established. SPSS was used to analyze the data presented. The findings were presented using tables, explanations, and diagrams. Content analysis method was used for qualitative analysis purposes. Results: The questionnaires results indicated that majority, 128 (89%) of Mathematics and English teachers strongly agreed that the school was keen on ensuring that corporal punishment is not administered hence alternative ways so as to reduce mental effect such as cognitive deficits (mean of 5). Nevertheless, 68(47%) strongly disagreed and 38(26%) disagreed that there were systems in school for students to speak out when they are undergoing physical and mental torture (mean of 2). On the interview results, principals and counseling teachers indicated that students with executive functions disorder got bullied, had low self-esteem, indiscipline issues such as fighting the students laughing at their weaknesses, and got low grades. The intervention measures implemented by the school included observing and singling out cases. The R value was 0.943 and the R-square was 0.890. This meant that executive functioning disorder had an 89% influence on vulnerability to depression whereas 11% was as a result of other factors not addressed in the study. The significance value was 0.000 hence below 0.05. This made the study reject the null hypothesis that executive functioning deficits have no statistically significant effect on vulnerability to depression among adolescents in secondary school in Meru County, Kenya. Conclusion: Though there were awareness campaigns on mental issues as a result of drug and substance abuse, there still lacked awareness made on mental issues due to cognitive deficits making students unable to multitask, manage time and lack attention. This lack of awareness was caused due to unavailability of systems and communication channels that students suffering from cognitive deficits could speak up on to get help. Recommendations: The study recommends that on executive function disorder, the management of the school should beef up on creating awareness of how mental issues can lead to drug and substance abuse by the students. There should be provision of finances by the ministry of education to schools to be able to have print media such as posters, magazines, newsletters and pamphlets on what executive function disorders are, how can one tell they suffer from them and the various treatment methods in place.